Chemical and rheological evaluation of aging properties of high content SBS polymer modified asphalt. (15th September 2019) - Yan, Chuanqi; Huang, Weidong; Lin, Peng; Zhang, Yuan; Lv, Quan
Graphical abstract: Highlights: Short-term aging will damage the rutting-resistance of HCPMA. A strong correlation between carbonyl content and SBS degradation level was found. A polymer-domination phenomenon was observed in rheology test. J3.2 was more sensitive to SBS degradation compared with G*/sin δ. Modulus, phase angle and Jnr values can be well-predicted using infrared functional indices. Abstract: High content SBS polymer modified asphalt (HCPMA) is now widely employed in Open-Graded Friction Course (OGFC), but its aging behavior has not yet been well understood due to its high polymer content and consequently high construction temperature. In this study, HCPMA were aged at various temperatures and durations in the laboratory and the chemical and rheological evolutions during aging were tracked using Gel Permeation Chromatography (GPC), Fourier Transform Infrared (FTIR), dynamic shear oscillatory test, master curve and multiple stress creep and recovery test. GPC and FTIR results show that generally the polymer degradation happens at the initial stage of aging. Rheology tests highlight an interesting finding that aging will push the HCPMA to a less elastic end, which is due to the softening effects of polymer degradation. It is found that among all aging conditions, HCPMA yields the least elastic response after the standard Pressure Aging Vessel aging. Moreover, Principal Component Analysis shows that the 9 popular parameters employed in this study (such as modulus, phase angle, Jnr3.2 and etc.) have a lot in common and can be explained by two variables: asphalt oxidation level and SBS content. By using these two variables, the evolution of HCPMA modulus and phase angle after aging can be well predicted with an exponential regression and a linear regression, respectively. The research findings provide insights to better understand the aging properties of HCPMA.